THE INDOMITABLE LADY DOCTORS (Author: Carlotta Hacker) - Wright, Isobel (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1975)
Carlotta Hacker. THE INDOMITABLE LADY DOCTORS. Toronto: Clarke. Irwin. 1974. 259 pp. Illus. Index. $8.50.